The Diligent Bidder in Public Works Contracts - Seminario Córdova, Renzo (2015)
The author explains what «diligent bidder» means during bidding processes. First, he starts analyzing some civil law matters as due diligence and compliance with obligations. Then, he states his position about whether the consultation during bidding processes is a right or an obligation for the bidder, and under what conditions it would work. Furthermore, he explains the relevance of identifying strict liability on developing the technical file to set the compensation of damages. Finally, the author offers some cases to determine when contractors are «diligent bidders» and when they are not. He points out that when contractors are «diligent bidders», the owner must take full responsibility; on the other hand, when they are not «diligent bidders» and they partially caused the damage, the judge or the arbitrator should reduce the compensation.